RNase P-Mediated Sequence-Specific Cleavage of RNA by Engineered External Guide Sequences - Merel Derksen; Vicky Mertens; Ger J.M. Pruijn (Biomolecules, 2015)
The RNA cleavage activity of RNase P can be employed to decrease the levels of specific RNAs and to study their function or even to eradicate pathogens. Two different technologies have been developed to use RNase P as a tool for RNA knockdown. In one of these, an external guide sequence, which mimics a tRNA precursor, a well-known natural RNase P substrate, is used to target an RNA molecule for cleavage by endogenous RNase P. Alternatively, a guide sequence can be attached to M1 RNA, the (catalytic) RNase P RNA subunit of Escherichia coli. The guide sequence is specific for an RNA target, which is subsequently cleaved by the bacterial M1 RNA moiety. These approaches are applicable in both bacteria and eukaryotes. In this review, we will discuss the two technologies in which RNase P is used to reduce RNA expression levels.